The Preparation of an Artificial Reagent for the One-Stage Factor VIII Assay - Nyman, D (Thrombosis and Haemostasis, 1970)
A method for preparation of an artificial substrate for the one-stage factor VIII assay is described. Standardization of the test is given. The method is specific and reproducible.